Glia in Health and Disease - Spohr, Tania (IntechOpen, 2020)
The book will highlight the role played by glial cells in the central and peripheral nervous systems in both healthy and unhealthy individuals. Among all processes involved, we will discuss the importance of the enteric nervous system in the control of gut homeostasis, in the interaction with the immune system, and its participation in pathological conditions such as metabolic syndrome. We will also look at the relevance of astrocytes during synaptic transmission and the regulation of plasticity by releasing gliotransmitters. Ultimately, we will highlight the influence of astrocytes during the development of a number of neurodegenerative diseases, such as multiple sclerosis and Alzheimer's disease, focusing on how the serum levels of the astrocytic protein S100B can be used as a biomarker for clinical decisions.